The Influence of Environmental Cost and Carbon Productivity on Profitability: The Mediating Role of Green Innovation - Satrio Ashif Kevin Meikoko; Afni Sirait (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to examine the influence of environmental cost and carbon productivity on company profitability, with green innovation as a mediating variable. The sample comprises 54 firm-year observations from 18 basic industry sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that green innovation does not mediate the effect of environmental cost or carbon productivity on profitability. However, environmental cost has a significant direct effect on profitability (negative direction), while carbon productivity has no significant effect. In addition, green innovation itself exerts a significant positive influence on profitability. These findings suggest that environmental investment directly impacts firm profits and green innovation can enhance profitability, whereas improving carbon productivity alone has not yet produced a tangible financial impact. Practically, this study provides insights for manufacturing firms in formulating sustainability strategies that balance environmental cost, carbon productivity, and green innovation to optimize profitability.